An Evaluation of the Word Classes Primary School Fourth-Grade Students Use in Their Writing Practices - Esra SEVER; Ezgi ÇETİNKAYA ÖZDEMİR (Elementary Education Online, 2023)
In this study, the texts of Health and Environment and Our Values themes in the fourth-grade Turkish textbook were studied and students performed writing practices regarding these themes. Designed as a descriptive survey study, this research aims to investigate the variety of word classes in their texts during writing practices. 28 fourth-grade students from a public school in Zonguldak participated in the study. Writing practices regarding eight texts included in the themes were conducted each week and 228 texts were obtained during the study. Content analysis was used to analyze the data. The students’ texts were digitalized and word lists were created for each student using the Simple Concordance Program 4.07 software. The results indicated that the participants use noun, verb, and adjective more among the word classes in the writing practices regarding the Health and Environment theme. In the writing practices regarding the Our Values theme, the female students were found to use noun, verb, and pronoun more among the word classes and the male students were found to use noun, verb, and adverb more among word classes. Considering the number of words used in the eight different word classes, a difference was determined in favor of females in both themes